Question
upstudy study bank question image url

8. Solve each system of equations using Clearly give the matrix and solution. U \( \left\{\begin{array}{l}10 x+12 y=6 \\ 7 x-3 y=-30\end{array}\right. \)

Ask by Munoz Sanders. in the United States
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution is \( x = -3 \) and \( y = 3 \).

Solution

Solve the system of equations \( 10x+12y=6;7x-3y=-30 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}10x+12y=6\\7x-3y=-30\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{3-6y}{5}\\7x-3y=-30\end{array}\right.\) - step2: Substitute the value of \(x:\) \(7\times \frac{3-6y}{5}-3y=-30\) - step3: Simplify: \(\frac{7\left(3-6y\right)}{5}-3y=-30\) - step4: Multiply both sides of the equation by LCD: \(\left(\frac{7\left(3-6y\right)}{5}-3y\right)\times 5=-30\times 5\) - step5: Simplify the equation: \(21-57y=-150\) - step6: Move the constant to the right side: \(-57y=-150-21\) - step7: Subtract the numbers: \(-57y=-171\) - step8: Change the signs: \(57y=171\) - step9: Divide both sides: \(\frac{57y}{57}=\frac{171}{57}\) - step10: Divide the numbers: \(y=3\) - step11: Substitute the value of \(y:\) \(x=\frac{3-6\times 3}{5}\) - step12: Calculate: \(x=-3\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-3\\y=3\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-3\\y=3\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(-3,3\right)\) The solution to the system of equations is \( (x, y) = (-3, 3) \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the system of equations using matrices, we first represent the equations in matrix form \(Ax = b\). Here, the matrix \(A\) is: \[ \begin{pmatrix} 10 & 12 \\ 7 & -3 \end{pmatrix} \] The vector \(x\) is: \[ \begin{pmatrix} x \\ y \end{pmatrix} \] And the vector \(b\) is: \[ \begin{pmatrix} 6 \\ -30 \end{pmatrix} \] Next, we can use the inverse of matrix \(A\) (if it exists) to find \(x\) by computing \(x = A^{-1}b\). After calculating, we find the solution to be \(x = -6\) and \(y = 9\). To present the solution clearly: \[ \begin{pmatrix} x \\ y \end{pmatrix} = \begin{pmatrix} -6 \\ 9 \end{pmatrix} \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy